Effects of different types of high-definition transcranial electrical stimulation on visual working memory and contralateral delayed activity - Yinan Ai; Mingyu Yin; Liying Zhang; Haojie Hu; Haiqing Zheng; Wuwei Feng; Yixuan Ku; Xiquan Hu (Journal of NeuroEngineering and Rehabilitation)
Abstract Background and purpose Working memory is critical for individuals and has been found to be improved by electrical stimulation of the left dorsolateral prefrontal cortex (DLPFC). However, the effects of different types of transcranial electrical stimulation on working memory are controversial, and the underlying mechanism remains uncertain. In this study, high-definition transcranial direct current stimulation (HD-tDCS) and high-definition transcranial random noise stimulation (HD-tRNS) were applied to the DLPFC to observe the different effects on visual working memory (VWM). The aim was to explore the causal relationship between the electrical activity of the DLPFC and the posterior parietal cortex (PPC) electrical activity and the contralateral delayed activity (CDA). Methods Thirty-three healthy subjects received HD-tDCS, HD-tRNS and sham stimulation in a random order. Stimulation was applied to the left DLPFC for 20 min. The subjects underwent a color change-detection task as our VWM task and an auditory digit span test (DST) immediately after stimulation. Event-related potential (ERP) data were collected during the VWM task. Results The results revealed significant differences between the different types of HD-tES. There was a remarkable increase in VWM capacity following HD-tDCS compared with both HD-tRNS (p a = 0.038) and sham stimulation (p a = 0.038). Additionally, the CDA from the PPC differed after stimulation of the DLPFC. Both HD-tDCS and HD-tRNS expanded the maximum CDA amplitude from set size of 4 to 6, whereas after sham stimulation, the maximum CDA was maintained at a set size of 4. Compared with the sham condition, only HD-tDCS induced a noteworthy increase in CDA amplitude (p a = 0.012). Notably, a significant correlation emerged between the mean CDA amplitude and VWM capacity (p < 0.001, r = − 0.402). Conclusion These findings underscore the ability of HD-tDCS to target the DLPFC to augment working memory capacity while concurrently amplifying CDA amplitudes in the PPC through the frontoparietal network. Trial registration ChiCTR2300074898.